The development of a sustainable climate resilience building framework for Southern Zimbabwe - Rameck Defe; Mark Matsa; Veronica Makuvaro (Nature-Based Solutions)
Resilience building has increasingly been embraced as a framework for managing climate change and variability induced disaster. The study sought to develop a Sustainable Climate Resilience Building framework for managing climate change adversities in Mwenezi District of Southern Zimbabwe. A mixed method approach which utilized both qualitative and quantitative techniques was used. The choice of two approaches was based on a phenomenological constructivist belief that problems are best solved using multiple sources. The qualitative approach depended on questionnaires, interviews, focus group discussions and direct field observations. The quantitative approach depended on closed ended questions and use of statistical package for social scientists (SPSS version 25.0) for data analysis. Qualitative data was subjected to content analysis. The findings obtained revealed that Non-Governmental Organizations and Government Departments have collaborated and initiated resilience interventions to manage climate change impacts. Some of the interventions implemented can be categorized as crop production and livestock production interventions. However there are some challenges obtained hindering communities’ capacity to build resilience these are namely, ignorance, lack of technical know-how and lack of financial resources to buy resilient inputs on the side of communities. Based on the findings, a Sustainable Climate Resilience Building framework was developed to manage climate change adversities. The researchers recommend communities to adopt a Sustainable Climate Resilience Building framework. This is because the framework provides a pathway for building community resilience to effectively manage climate change adversities.